Direct Numerical Simulations of Magnetic Helicity Conserving Astrophysical Dynamos - Cridland, Alex J. (My University, 2014)
Here we present direct numerical simulations of a shearing box which models the MHD turbulence in astrophysical systems with cylindrical geometries. The purpose of these simulations is to detect the source of the electromotive force - the driver of large scale magnetic field evolution. This electromotive force is responsible for the large scale dynamo action which builds and maintains the magnetic field against dissipation in plasmas. We compare the estimates of the electromotive force from the kinematic approximation of mean field theory - the most prevalent theory for astrophysical dynamos - with a modified version of mean field theory which restricts the electromotive force by the consideration of magnetic helicity conservation. We will show that in general the kinematic approximation overestimates the observed electromotive force for the majority of the simulation, while the term derived from the helicity conservation estimates the electromotive force very well. We will also illustrate the importance of the shear in the fluid to the growth and strength of the resulting large scale magnetic field. Too strong and the small scale dynamo does not grow enough to properly seed a strong large scale dynamo. Too weak, and no large scale magnetic field is observed after the small scale dynamo has saturated. Finally, we will find that in order to maintain the strength of the emerged large scale magnetic dynamo we require a magnetic Prandtl number ($Pr \equiv \nu/\eta$) that is at least an order of magnitude above unity.
Keywords: Astrophysics; Magnetohydrodynamics; MHD; dynamo theory; direct numerical simulation; Physical Processes; Physical Processes